A Systemic Conceptualization of Intimate Partner Violence: Attachment and Differentiation. (July 2020) - Katafiasz, Heather
Intimate partner violence (IPV) is a national public health concern that is often conceptualized individually. This article provides a systemic understanding of IPV through the separate and combined lens of Bowen family systems and Attachment Theories. A brief individual overview and application to IPV is provided for each theory, followed by a conceptual integration and then an application of the two theories combined to a case example.